Quantification of long-term primary and secondary source contributions to carbonaceous aerosols. (December 2016) - Shi, Guoliang; Peng, Xing; Liu, Jiayuan; Tian, Yingze; Song, Danlin; Yu, Haofei; Feng, Yinchang; Russell, Armistead G.
Abstract: Ambient fine particulate matter samples were collected during 2009–2013 in Chengdu, a megacity in western China, and the samples were speciated into organic carbon (OC), elemental carbon (EC), char-EC, soot-EC, eight carbon fractions, inorganic elements and water-soluble ions. Char-EC and soot-EC contribute to the better understanding of the sources and properties of EC. The highest levels of most carbon fractions were found in winter and May. The higher OC/EC ratio in winter suggests higher SOC fraction in winter, and higher char-EC/soot-EC ratio in May are the direct consequences of straw burning activities. Source contributions to PM2.5 and carbonaceous aerosols were quantified using the ME2 receptor model. Major contributors to OC in PM2.5 are vehicular exhaust (36.5%), coal combustion & straw burning (35.2%) and SOC (27.0%). The first two categories also contributed 51.4% and 49.3% of char-EC in PM2.5 . Vehicular exhaust dominated soot-EC, contributing 63.0% to soot-EC in PM2.5 . SOC contributed to high OC levels in winter due to the increase of precursor emissions and stable meteorological conditions. Coal combustion & straw burning show higher contributions to OC, char-EC and soot-EC in winter months and in May, which can be explained, in part, by increased coal consumption in winter and straw burning activities in May. Vehicular exhaust contributions are not strongly associated with monthly nor weekday-weekend patterns, resulting in that soot-EC vary insignificantly by month nor by weekday. Graphical abstract: Highlights: Carbonaceous species in PM were measured during a long-term observation in China. Carbon fractions peak in winter and May, due to coal consumption and straw burning. ME2 was used to quantify long-term contributions to size-segregated carbon aerosol. OC and char vary by month, while soot vary insignificantly by month nor by weekday. Abstract : Source contributors to OC, char-EC and soot-EC in PM2.5 were quantified and their seasonal variations were analyzed.